Synthesis of Interleukin-10 in Patients with Ulcerative Colitis and Helicobacter pylori Infection - Jesús K. Yamamoto-Furusho; Gabriela Fonseca-Camarillo; Carlos A. Barrera-Ochoa; Janette Furuzawa-Carballeda (Gastroenterology Research and Practice)
Background/Aims. Epidemiological evidence suggests a relationship between Helicobacter pylori infection with the development of autoimmune diseases. H. pylori elicit a chronic systemic inflammatory response with the secretion of proinflammatory cytokines. IL-10 is a regulatory cytokine that plays a central role in limiting host immune response to pathogen. Increased IL-10 levels were reported in H. pylori–infected gastric mucosa. The aim of this study was to explore the relationship between IL-10 systemic synthesis and H. pylori infection in patients with ulcerative colitis. Methods. Detection of H. pylori infection was performed by a 13C-urea breath test in 31 patients with UC. In each patient, a serum sample was drawn to measure IL-10 by the ELISA technique. Based on the primary breath test result, two groups were formed and serum IL-10 was measured. Results. Serological IL-10 levels in patients with UC and negative 13C-urea breath test was 10.28 pg/ml whereas in patients with UC and positive 13C-urea breath test was 5.5 pg/ml (P=0.035). IL-10 levels were higher in the inflammatory endoscopic and histological active groups which tested positive in the 13C-urea breath tests for H. pylori (P<0.05).Conclusions. The role of IL-10 secretion in patients with UC in determining the clinicopathological outcome of infection merits further study. This study suggests an association between serum IL-10 and disease severity in patients with UC and HP infection.